The Impact of Workforce Skills on the Choice of Location of Enterprises from the Business Process Outsourcing/ Shared Service Center Sector - Tomasz Kijek; Katarzyna Budzyńska (Przegląd Prawno-Ekonomiczny)
Human capital consists of knowledge, skills, and competences innate or acquired by employees working in the organization. This article deals with the issue of the effect of human capital on the location decisions of enterprises from the BPO/SSC sector. We focused on two main components of human capital, i.e., soft skills and hard skills, which are crucial location factors for the BPO/SSC enterprises. The research instrument was the questionnaire containing questions regarding location factors of enterprises from the BPO/SSC sector. The research sample consisted of 58 enterprises. The principal component analysis and the linear regression were used to conduct analyses. Our findings show that only soft skills have the impact on the choice of location by offshoring companies.